(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2020)
The study investigated commonly used abbreviated words among the sampled population. It also determined the difference between those that abbreviated words and those that did not abbreviated words. The study revealed the list of abbreviated words in the study. And also ascertained which gender abbreviated words most. These were with a view to provide information on the implications of SMS language on English Language writing and learning of the students. The study adopted quantitative survey research design. The population for the study Comprised 83 senior secondary school students in Olorunda Local Government, Osun State. The sample size comprised 100 respondents, selected using multistage sampling technique. One Local Government Area (LGA) was selected from thirty Local Governments in the state using simple random sampling technique. From the LGA, four senior secondary school was selected using simple random sampling technique and from each school, 25 students were selected from senior secondary school II using simple random sampling technique. The students were taught for forty minutes on how to write a letter devoid of using abbreviated words and after the lesson, the students were asked to write a letter to their father informing him about social amenities in your school. Those letters were collected, marked and converted to data for this study. Data collected was analyzed using simple percentages. Those letter were collected, marked and converted to data for this study. The result showed commonly used abbreviated words by the respondents such as, pls (please) 9 times by 9 students, u (you) 26 times by 10 students , and fyn (fine) 5 times and so on. The result also revealed 51 students (representing 61.4%) did not abbreviated words in the letter writing and 32 students (representing 38.6%) abbreviated words in the letter. The result showed that female gender was the gender that abbreviated words most in the letter with 49% and male with 35%. Lastly, the result also revealed percentage of students that used abbreviated words 38.6% of the students used abbreviated words while 61.4% of the 100% total population did not used abbreviated words The study concluded that use of abbreviated words did not have effect on English language learning and writing among secondary school students in Olorunda Local Government, Osun State.